Quality improvement initiatives in fragility fracture care and prevention - Mitchell, PJ; Cooper, C; Fujita, M; Halbout, P; Åkesson, K; Costa, M; Dreinhöfer, KE; Marsh, DR; Lee, J-K; Chan, D-CD; Javaid, MK (Springer, 2019)
Purpose of Review This review sought to describe quality improvement initiatives in fragility fracture care and prevention.